2022
DOI: 10.3390/pharmaceutics14040719
|View full text |Cite
|
Sign up to set email alerts
|

Diphlorethohydroxycarmalol Derived from Ishige okamurae Improves Behavioral and Physiological Responses of Muscle Atrophy Induced by Dexamethasone in an In-Vivo Model

Abstract: Muscle atrophy refers to the loss of skeletal muscle mass, myofiber size, and related physical functions such as walking speed or grip strength caused by aging or a lack of physical activity due to injury or illness and can also be attributed to excessive exposure to corticosteroids. Ishige okamurae (IO) and its active component, diphlorethohydroxycarmalol (DPHC), have been known to improve glucose homeostasis by controlling the contraction of skeletal muscles. Based on this idea, we hypothesized that the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
(50 reference statements)
0
7
0
Order By: Relevance
“…In addition, PI3K mRNA levels were elevated in the soleus muscle tissues in the IPA group. Ryu et al ( 21 ) found that IOE and its active component DPHC improved grip strength and ladder climbing responses and preserved lean mass of calf muscle atrophy induced by dexamethasone (DEX) in vivo . Also, treatment with IOE or DPHC restored the DEX-mediated reductions in PI3K and Akt mRNA levels in the gastrocnemius muscle, which increased protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, PI3K mRNA levels were elevated in the soleus muscle tissues in the IPA group. Ryu et al ( 21 ) found that IOE and its active component DPHC improved grip strength and ladder climbing responses and preserved lean mass of calf muscle atrophy induced by dexamethasone (DEX) in vivo . Also, treatment with IOE or DPHC restored the DEX-mediated reductions in PI3K and Akt mRNA levels in the gastrocnemius muscle, which increased protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…IO extracts (IOE) are known to have anti-obesity by inhibiting lipid accumulation and anti-diabetic effects by improving insulin resistance and protecting pancreatic β-cells dysfunction in vitro and vivo ( 16 , 17 ). Lately, IO extract (IOE) has been reported to promote the pathway to synthesis of muscles through the myostatin/Smad3 pathway and enhance protein phosphorylation of the growth regulatory axis in vitro ( 18 20 ) and increase muscle mass and strength in vivo ( 21 ). IOE showed no significant toxicity in vivo or animal models ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the gastrocnemius and soleus muscles were harvested in accordance with the ethical principles of the Institutional Animal Care and Use Committee of Gachon University (approval no. LCDI-2020-0003) [ 50 ].…”
Section: Methodsmentioning
confidence: 99%
“…Functional nutrient supplementation is safe with few side effects, and it can be used in patients with an inherent risk of weakness [32]. Alleviation of muscle wasting by IO and its active substance DPHC has been previously reported in an in vivo study that utilized dexamethasoneinduced muscle atrophy model and 14-month-old aging female murine model [19,20].…”
Section: Seaweed Consumption and Aging-associated Muscle Lossmentioning
confidence: 95%
“…It improved muscular insulin resistance in vitro. IO treatment enhanced the protein synthesis pathway and the recovery of muscle atrophy due to dexamethasone chemical-induced muscle disorders in vivo in male mice [20,21]. Both IO and DPHC were able to reverse the aging parameters and sex hormonal imbalance, in 14-month-old female C57BL/6J mice [19].…”
mentioning
confidence: 92%